Review of the employee performance evaluation system at the Directorate General of Taxes: Its effectiveness and employee satisfaction level - Anies Said Basalamah; Herru Widiatmanti (Directorate General of Taxes, 2023)
This quantitative research seeks to determine the effectiveness of the Directorate General of Taxes (DGT) performanceevaluation system, measure how satisfied the employees are, and to prove differences among different categories ofemployees. This research is an extension of the study by Widiatmanti (2020) on 1,587 DGT employees. Analysis ofVariance (ANOVA) and Exploratory Factor Analysis (EFA) were used to analyze the data in addition to descriptive dataanalysis. Generally, respondents feel the system is quite effective, and they are quite satisfied, except for three variablesthat most respondents strongly disagree with and relate to the performance status of SABCD and the level 1 and level2 ranking sessions. ANOVA method indicates that there are indeed differences among different categories of employees,while EFA method reveals that despite seven insignificant variables, none of them suggests the need to change DGTRegulation 12/PJ/2018, including its SABCD performance status. However, the need for change or adjustments arisesbecause there are provisions at higher levels of regulation: Government Regulation and two ministerial decrees.Therefore, we suggest that the use of forced rank in the SABCD performance status is abolished and replaced mainlydue to excellent, moderate, and poor performances.